2016
DOI: 10.1093/jac/dkw337
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of KPC-producingKlebsiella pneumoniaefrom invasive infections in Italy: increasing diversity with predominance of the ST512 clade II sublineage

Abstract: Although a trend to a polyclonal evolution of the Italian KPC-KP was noted, this study showed that the KPC-KP population remained largely oligoclonal with the wide diffusion of an ST512 lineage carrying cps-2 capsular type and producing the KPC-3 enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
55
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 37 publications
(44 reference statements)
14
55
2
Order By: Relevance
“…The most important mechanism in carbapenem resistance in Enterobacteriaceae is the production of carbapenemases, primarily KPC VIM NDM and OXA-48 types, which display remarkable geographycal variability. KPC production is the most frequent mechanism of resistance to carbapenems in K. pneumoniae in Italy, as already reported in the 2011 Italian survey [4] and KPC-type carbapenemases-producing K. pneumoniae has become endemic, as very recently confirmed [5]. Underlying haematological disease, intensive chemotherapy, neutropenia, gastrointestinal mucositis and prolonged hospitalization are all conditions favouring the CRKP spread and infections, mainly bacteremias [611].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The most important mechanism in carbapenem resistance in Enterobacteriaceae is the production of carbapenemases, primarily KPC VIM NDM and OXA-48 types, which display remarkable geographycal variability. KPC production is the most frequent mechanism of resistance to carbapenems in K. pneumoniae in Italy, as already reported in the 2011 Italian survey [4] and KPC-type carbapenemases-producing K. pneumoniae has become endemic, as very recently confirmed [5]. Underlying haematological disease, intensive chemotherapy, neutropenia, gastrointestinal mucositis and prolonged hospitalization are all conditions favouring the CRKP spread and infections, mainly bacteremias [611].…”
Section: Introductionmentioning
confidence: 84%
“…The diffusion of carbapenem-resistant Klebsiella pneumoniae (CRKP) [15] in the setting of patients with haematological malignancies undergoing intensive myelosuppressive chemotherapy is a very worrying challenge [611], especially in endemic areas. The most important mechanism in carbapenem resistance in Enterobacteriaceae is the production of carbapenemases, primarily KPC VIM NDM and OXA-48 types, which display remarkable geographycal variability.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, very similar pulsotypes were recently observed for K . pneumoniae isolates included in a recent surveillance study conducted in Italian hospitals, suggesting the persistence of the two clonal lineages in our country [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrated that strains of ST258 are hybrid clones originated by a number of large genomic recombination events that gave rise to two major clades (clade I and clade II), characterized mainly by different capsule polysaccharide (CPS) gene clusters 13–15 . Clade II strains contribute to the majority of ST258 and of other STs of CG258 causing outbreaks reported in several regions including USA, Italy, South America, Israel and Greece 14, 1620 .…”
Section: Introductionmentioning
confidence: 99%